Multiresponse model based design parameters optimization: engineering approach - Popov, S.A.; Abramov, A.M. (EAI Endorsed Transactions on Energy Web, 2017)
A practical algorithm of determination of the set of Pareto optimal output parameters and a solution of the reverse optimization problem have been proposed. Basics of building and usage of multiresponse model are presented, which allows to perform multicriteria optimization optimization for different design and manufacturing situations.